Research of the Electric Drive with Intermittent Motion Law - N. A. Voronina; A. D. Umurzakova; L. A. Payuk; K. V. Khatsevskiy (Омский научный вестник)
An electric drive with an intermittent law of the shaft motion of the executive motor, which is widely used in various fields of industry, is considered. The aim of the study is to determine the ways of generating supply voltages or currents to the adjustment characteristics of the electric drive. In this work, it is necessary to determine the output parameters: electromagnetic moment, angular velocity and coordinates of the moving element of the working body. The study applied the method of mathematical modeling. The results of the work are the time dependences of the output parameters and the adjustment characteristics of the electric drive with an intermittent law of motion of the shaft of the actuating motor. Based on the results obtained, it can be concluded that with the phase method of generating supply currents or voltages, it is necessary to control the electric motor along one of the windings.